Comparison of the Efficacy of Nonsteroidal Anti-Inflammatory Drugs and Opioids in the Treatment of Acute Renal Colic: A Systematic Review and Meta-Analysis - Leng, Xie-Yuan; Liu, Chang-Ning; Wang, Shi-Chan; Peng, Hao-Dong; Wang, De-Guang; Pan, Hai-Feng (Frontiers in Pharmacology, 2022)
Background: Although multiple randomized controlled trials (RCTs) and systematic review and meta-analysis were performed to investigate efficiency and safety of NSAIDs and opioids in treatment for acute renal colic, the therapeutic regimen of renal colic is still controversial. Therefore, the aim of this study was to derive a more concise comparison of the effectiveness and safety between NSAIDs and opioids as treatment for patients with acute renal colic by a systematic review and meta-analysis. Design: We searched PUBMED, EMBASE, and Cochrane Central Register of controlled trials for seeking eligible studies. Pooled mean difference (MD) and risk ratio (RR) with 95% confidence interval (CI) was calculated using random-effects model. Results: Seventeen studies involving 2,881 participants were included in the systematic review and meta-analysis. No significant difference between NSAIDs and opioids group was observed with changes in visual analogue scale (VAS) at 0 to 30 minutes (MD=0.79, 95%CI: -0.02, 1.61). However, NSAIDs in the form of intravenous (IV) had beneficial effect on changes in VAS at zero to thirty minutes, comparing to opioids (MD= 1.25, 95%Cl: 0.31, 2.18). NSAIDs group in the form of intravenous greatly improves former outcome compared to opioids group, as well as VAS at 30 minutes (MD= -1.33, 95%Cl: -2.06, -0.59; MD= -1.45, 95%Cl: -2.81, -0.09, respectively). Moreover, the similar results of this outcome were also seen with VAS at 45 minutes (MD= -1.36, 95% Cl: -1.96, -0.77). Besides, there was statistical difference in the incidence of later rescue (RR=0.74, 95%CI: 0.66, 0.83), drug-related adverse events (RR=0.40, 95%CI: 0.26, 0.61), dizziness (RR=0.71, 95%CI: 0.75, 1.40) and vomiting (RR=0.10, 95%CI: 0.0, 1.32), respectively. Conclusion: NSAIDs have more advantages, considered as first-line agent for pain relieving with renal colic, in many outcomes (e.g. VAS over different period, side-effects related drugs) focused on in this study. However, the patients with treatment of NSAIDs clinicians used in the form of intravenous get benefit from primary outcome (changes in VAS at 0 to 30 minutes) and VAS at 60 minutes.